Improving Editorial Text Writing Ability Through Problem Based Learning Methods in High School Students - Nurdahlia, Nurdahlia; Sari, Esti Swatika (UNIVERSITAS PAKUAN, 2025)
This study aims to find out the improvement the learning process of writing students' editorial texts using the problem-based learning method and the results of students' ability to write editorial texts using the problem-based learning method of class XII-MIA SMAN 2 Tana Tidung. This research is a classroom action research. The subject of this class action research is class XII-MIA students of SMA Negeri 2 Tanah Tidung which totals 30 people, consisting of 7 male students and 23 female students. The research was carried out in two cycles consisting of four stages of each cycle, namely planning, implementation of actions, observation, and reflection. The data collection techniques used in this study are in the form of questionnaires, observations, interviews, field notes, photo documentation, and writing assessment sheets. The data obtained were analyzed in a qualitative descriptive manner supported by quantitative data. The results of the study: (1) there was an increase in the learning process using the problem based learning method in writing editorial texts for students of class XII-MIA SMAN 2 Tana Tidung which was shown by activeness, attention to lessons, enthusiasm, courage to appear in front of the class, and group cooperation so as to create a fun, active, and creative learning atmosphere, (2) an increase in the ability to write editorial texts using the problem based learning. The ability to write editorial text in the pre-action stage gets an average score of 49. In the first cycle, the average score was 75, and the second cycle obtained an average score of 86.